Dartseq SNP genotypes for catla (SNP discovery for panel development) - Hamilton, Matthew (2023)
Dartseq single nucleotide polymorphism (SNP) discrete genotype calls for WorldFish catla genetic improvement program generation zero (G0, base population) individuals used as parent parents. These data were generated to identify additional SNP to be used in the development of parentage assignment tools.